Evaluation of Drug Information Service provided by Clinical Pharmacy Department based on Provider and Enquirers' Perspective - V.G, Kuchake; O.D, Maheshwari; S.J, Surana; P.H, Patil; P.N, Dighore (Indian Journal of Pharmacy Practice)
Hypertension is not a disease but an important risk factor for cardiovascular complication. This type of medical audit and appropriate feedback on usage of antihypertensive medications may greatly assist the health care providers in rational use of medications.The objective of this study was to evaluate the prescribing pattern and drug utilisation of antihypertensive medications in uncomplicated hypertension. Observational and Prospective study was performed at Indira Gandhi Memorial Hospital, Shirpur, Maharashtra in India. Total 5025 patients visited the medicine ward of Indira Gandhi Memorial Hospital. Among them 244 patients had uncomplicated hypertension. st st From 1 July, 2008 to 31 December, 2008 Hypertensive medications were divided into 2 main categories; Monotherapy and Combination therapy was defined and discussed separately. During 6 months study period, 510 prescriptions were collected, among them 244 including (132) female & (112) male patients were as per inclusion criteria. Among them, 150 patients were on mono therapy which included 78 female & 72 male patients, comprising 54%(81) on Calcium Channel Blockers, 24.67%(37) on â-Blockers, 11.33%(17) on Angiotensin Receptor Blockers, 6%(9) on Angiotensin Converting Enzyme Inhibitors, 4%(6) on Diuretics respectively, and 38.52% (94) patients on combination therapy. In the view of drug utilisation, it was observed that, the diuretics are less prescribed and calcium channel blockers are frequently prescribed medications in management of hypertension. So, it requires further improvement of prescription pattern of antihypertensive medication for better patient health care
Keywords: Anti-hypertensive drugs; drug utilisation; hypertension; prescribing pattern